2021
DOI: 10.3390/toxins14010009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prolonged Serotonin and Ergovaline Pre-Exposure on Vasoconstriction Ex Vivo

Abstract: Ergot alkaloid mycotoxins interfere in many functions associated with serotonergic neurotransmitters. Therefore, the objective was to evaluate whether the association of serotonin (5-hydroxytryptamine, 5-HT) and ergot alkaloids during a 24 h pre-incubation could affect the vascular contractile response to ergot alkaloids. To evaluate the effects of 24 h exposure to 5-HT and ergot alkaloids (ergovaline, ERV), two assays were conducted. The first assay determined the half-maximal inhibitory concentration (IC50) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…In the current study, increased concentrations of 5‐HT induced a contractile response greater than the pre‐contracted saphenous vein. This is similar to prior studies in cattle saphenous vein that evaluated 5‐HT without a pre‐contraction period (Klotz et al., 2012 , 2013 ; Valente et al., 2021 ). Notably, the 5‐HT concentration curve of the bovine lateral saphenous vein of the current study appears to be similar to the response observed by Watts (Watts, 2016 ) in the pre‐contracted rat tail artery in the presence of 5‐HT 2A and 5‐HT 1B antagonists.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, increased concentrations of 5‐HT induced a contractile response greater than the pre‐contracted saphenous vein. This is similar to prior studies in cattle saphenous vein that evaluated 5‐HT without a pre‐contraction period (Klotz et al., 2012 , 2013 ; Valente et al., 2021 ). Notably, the 5‐HT concentration curve of the bovine lateral saphenous vein of the current study appears to be similar to the response observed by Watts (Watts, 2016 ) in the pre‐contracted rat tail artery in the presence of 5‐HT 2A and 5‐HT 1B antagonists.…”
Section: Discussionsupporting
confidence: 89%
“…Dietary consumption of ergot alkaloids in toxic endophyte‐infected tall fescue has been shown to decrease vascular contractile responses to individual ergopeptine alkaloids, 5‐HT, and agonists selective for the 5‐HT 2A receptor in isolated bovine lateral saphenous veins and mesenteric blood vessels (Egert et al., 2014 ; Klotz et al., 2010 , 2012 , 2013 , 2016 , 2018 ). Additionally, increasing exposure of the isolated bovine lateral saphenous vein to ergovaline in vitro results in increased tissue concentrations of ergovaline, suggesting bioaccumulation of ergot alkaloids occurs in vascular tissue (Klotz et al., 2009 ; Valente et al., 2021 ). Ergot alkaloids can act as both agonists and antagonists of 5‐HT 2A ‐mediated vasoconstriction (Klotz et al., 2016 , 2018 ; Trotta et al., 2018 ), depending on the dose and duration of ergot alkaloid exposure (Trotta et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ergot alkaloids bind nonspecifically to vascular receptors ( Saper and Silberstein, 2006 ) such as the serotonin receptor, mediating peripheral vascular contracture ( Valente et al, 2022 ). However, POB is foremost an alpha-adrenergic antagonist ( Yoham, 2022 ); therefore, the present study supports the involvement of alpha-adrenergic receptors mediating arterial contraction after exposure to R- or S -epimers of ergot alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…A very specific pathology associated with ergot alkaloids and ergotism is a chronic vasoconstriction. Yonpaim et al [ 21 ] looked at the acute exposure of ergot alkaloids on vasoactivity in ovine vasculature, and Valente et al [ 22 ] evaluated prolonged ergot alkaloid exposure on the vasoactivity of bovine vasculature. Both studies [ 21 , 22 ] respectively evaluated aspects related to the ability of ergot alkaloids to interact with adrenergic and serotonergic receptors [ 23 ], and both papers concluded that receptor-mediated treatments for ergot alkaloid-induced vasoconstriction could be explored as potential therapies.…”
mentioning
confidence: 99%
“…Yonpaim et al [ 21 ] looked at the acute exposure of ergot alkaloids on vasoactivity in ovine vasculature, and Valente et al [ 22 ] evaluated prolonged ergot alkaloid exposure on the vasoactivity of bovine vasculature. Both studies [ 21 , 22 ] respectively evaluated aspects related to the ability of ergot alkaloids to interact with adrenergic and serotonergic receptors [ 23 ], and both papers concluded that receptor-mediated treatments for ergot alkaloid-induced vasoconstriction could be explored as potential therapies. From a systemic evaluation of ergot alkaloids’ impact on the whole animal or microbiome, to the study of a specific symptom, there is much yet to be learned about how ergot alkaloids disrupt mammalian physiology.…”
mentioning
confidence: 99%